Dopamine and Serotonin Modulate Free Amino Acids Production and Na+/K+ Pump Activity in Chinese Mitten Crab Eriocheir sinensis Under Acute Salinity Stress - Liu, Zhaoqun; Zhou, Zhi; Wang, Lingling; Li, Meijia; Wang, Weilin; Yi, Qilin; Huang, Shu; Song, Linsheng (Frontiers in Physiology, 2018)
The Chinese mitten crab Eriocheir sinensis has a complex life cycle and lives in saline or fresh water at different life stages, making it an ideal model to study the salinity adaptation of euryhaline animals. In the present study, next-generation sequencing, together with determinations of free amino acids (FAAs), monoamine neurotransmitters and Na+/K+ pump activity, were employed to understand the osmoregulatory mechanism in the hemocytes of Chinese mitten crab. After RNA-seq, a total of 15,138 differentially expressed genes were obtained from 12 transcriptome libraries. GO enrichment analysis revealed that the mRNA expression profiles were completely remodeled from 12 h to 24 h after salinity stress. The neuroendocrine system was activated under stimulation, and the monoamine neurotransmitters including dopamine (DA) and serotonin (5-HT) were released to modulate osmoregulation. Furthermore, the Na+/K+ pump in crab hemocytes was significantly inhibited post salinity stress, resulting in increased intracellular ion concentrations and osmotic pressure to sustain osmotic balance. Moreover, six key FAAs, including alanine (Ala), proline (Pro), glycine (Gly), glutamate (Glu), arginine (Arg) and aspartate (Asp), were overexpressed to modulate extracellular osmotic balance during salinity adaptation. Interestingly, the immune genes were not enriched in the GO analysis, implying that the immune system might not contribute fundamentally in the tolerance upon fluctuating ambient salinity in Chinese mitten crab. These results collectively demonstrated that Chinese mitten crab had evolved efficient regulation mechanism by modulating FAAs production and Na+/K+ pump activity to sustain osmotic balance independent of the immune system, in which the neuroendocrine modulation, especially generated by monoamine neurotransmitter, played an indispensable role.